Home Based Blood Pressure Monitoring in Indian Setting: A Consensus Document - Shetty, Sadanand (Journal of clinical and diagnostic research, 2018)
Hypertension is one of the most significant public health problem and a common lifestyle disease today in India. Monitoring of blood pressure along with appropriate and timely management is critical in order to avoid any morbidity and mortality associated with hypertension. The use of Home Blood Pressure Monitoring (HBPM) for the measurement of blood pressure by the patient outside the clinical setting, either at home or at work place, is increasing across the world. The practice of monitoring blood pressure at home is well accepted by the patients as well and can be a useful adjuvant to the routine office based blood pressure measurements. Recently, experts in the field of hypertension management across India were invited to develop a consensus document on the role of HBPM in the Indian setting. This consensus document reflects the views and suggestions of the experts who had participated in developing this document.